2002
DOI: 10.2190/mm78-xy3y-6lxr-0qdm
|View full text |Cite
|
Sign up to set email alerts
|

Disproportionate Clan Growth in Crow-Omaha Societies: A Kinship-Demographic Model for Explaining Settlement Hierarchies and Fissioning in the Prehistoric U.S. Southeast

Abstract: Ethnohistoric data on the Omaha tribe of Nebraska indicate that marriage practices favored the disproportionate demographic growth of ceremonially prominent clans while other clans remained small or decreased in population. Ultimately, this process may lead to a "crisis in exogamy" for the larger, more ceremonially active clans, which can lead to fissioning or social transformations. As a model, the disproportionate demographic growth among ceremonially prominent clans is suggested to account for the formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 19 publications
(6 reference statements)
0
13
0
Order By: Relevance
“…For example, of great interest are the correlations between the dwelling floor sizes and postmarital residence patterns detected by Melvin Ember (1973; see also Peregrine and Ember 2002), and further replicated and refined by Divale (1977), Brown (1987), Peregrine (2001), and Porčić (2010). However, the most sophisticated methodology for the identification of the basic features of the kin and family organization of ancient populations on the basis of the archeological data on ancient dwellings' characteristics and their patterns has been developed in the recent years by Bradley Ensor (2003Ensor ( , 2011Ensor ( , 2012Ensor ( , 2013aEnsor ( , 2013bEnsor ( , 2017.…”
Section: Fig 2 Identity Of Husband's Sister and Brother's Wife Withmentioning
confidence: 99%
“…For example, of great interest are the correlations between the dwelling floor sizes and postmarital residence patterns detected by Melvin Ember (1973; see also Peregrine and Ember 2002), and further replicated and refined by Divale (1977), Brown (1987), Peregrine (2001), and Porčić (2010). However, the most sophisticated methodology for the identification of the basic features of the kin and family organization of ancient populations on the basis of the archeological data on ancient dwellings' characteristics and their patterns has been developed in the recent years by Bradley Ensor (2003Ensor ( , 2011Ensor ( , 2012Ensor ( , 2013aEnsor ( , 2013bEnsor ( , 2017.…”
Section: Fig 2 Identity Of Husband's Sister and Brother's Wife Withmentioning
confidence: 99%
“…In an early use of HRAF codings, Chang (1958) discovered that (a) settlements for individual descent groups were always planned (with residences surrounding a central plaza and/or ceremonial features), (b) 82% of societies having settlements for multiple unilineal descent groups were planned and segmented (distinct descent group locations), and (c) settlements in societies with nonunilineal descent never had planned layouts, instead having widely dispersed residential groups (a ranchería settlement pattern), aggregated haphazard arrangements of residential groups, or rarely segmented villages. Ensor (2003aEnsor ( , 2013a generally corroborated these findings: Comparing settlement layouts in 62 North American cultures, he found that 100% of those with exogamous unilineal descent groups had formally planned settlements (residential areas surrounding a plaza), and that 97% with bilateral descent had informal settlement layouts (haphazard arrangements of residential groups or ranchería settlement patterns). Ensor (2013a) then used Pasternak's (1976) correlations on descent and residence to determine whether unilineal descent groups were matrilineal or patrilineal.…”
Section: Mid-level Theory: Materials Culture Residence and Descentmentioning
confidence: 85%
“…These mid-level generalizations can be used to empirically infer prehistoric kinship. The author has applied this technique to address problems in the Caribbean (Ensor, 2013c), the U.S. Southeast (Ensor, 2003a, in press), the Maya region (Ensor, 2013b), and the U.S. Southwest (Ensor, 2013a). Two cases are summarized here to illustrate archeological tests of the high-level theories described above.…”
Section: Mid-level Theory: Materials Culture Residence and Descentmentioning
confidence: 99%
“…There are no prescriptions in Crow-Omaha marital alliances. The alliances involve clan proscriptions only (Allen 2012:57-58;Ensor 2002Ensor , 2003Ensor , 2013aFox 1967;Lévi-Strauss 1965). There are at least two rules; both are proscriptions.…”
Section: Marital Alliancesmentioning
confidence: 99%
“…The Omaha people in the Late 19 th century adhered to the Omaha marital alliance system (Ensor 2003). To begin, I should note that there is no rule for moiety exogamy among the Omaha proper, whose moieties had cosmological, ceremonial, and gendered themes also represented in their clans' ceremonial themes (Ensor 2002;Fletcher andLa Flesche 1905-1906). Marriages were independent of moieties-some marital alliances were with clans in the same moiety and some were with clans in the opposite moiety (Ensor 2002(Ensor , 2003Fletcher andLa Flesche 1905-1906).…”
Section: Marital Alliancesmentioning
confidence: 99%